Evaluation of Medical Students’ Knowledge and Their Adherence to Safety Measures Regarding Solar Ultraviolet Exposure - Hana Hafalish, (AlQalam Journal of Medical and Applied Sciences, 2024)
Ultraviolet radiation, a type of electromagnetic radiation, can be released by both artificial and natural sources, including the sun. It is imperative to adopt the appropriate safety measures when close to an ultraviolet radiation source, as unprotected UV radiation exposure has been associated with a higher risk of developing various illnesses, such as skin tumors. This study aims to evaluate undergraduate medical students' knowledge of potential hazards from UV radiation exposure and their practice of safety measures. A cross-sectional study was conducted at Omar Al-Mukhtar University, Al-Beyda City, Libya. One hundred and nine medical students were involved in this study. The questionnaire examined participants' knowledge of and behavior toward potential risks associated with ultraviolet (UV) radiation exposure. Notably, 77.1% of them were female, and 22.9% were male. The majority of the respondents were more than 22 years old. Above half, 59.6% showed moderate knowledge about UV exposure consequences; most of the students, 91%, knew the side effects of UV on health, followed by 86%, who indicated that UV can cause premature aging and cancer. In contrast, less than a third knew that UV has a negative impact on the immune system, and about two-thirds (73.9%) didn't realize that sunburn can occur even on a cloudy day. Although medical students showed a moderate level of knowledge regarding UV radiation, there was a lack of active sun safety measures. الأشعة فوق البنفسجية ، وهي نوع من الإشعاع الكهرومغناطيسي ، من قبل كل من المصادر الاصطناعية والطبيعية ، بما في ذلك الشمس. من الضروري اعتماد تدابير السلامة المناسبة عندما تكون على مقربة من مصدر الأشعة فوق البنفسجية ، حيث ارتبط التعرض للأشعة فوق البنفسجية غير المحمية بزيادة خطر الإصابة بأمراض مختلفة ، مثل أورام الجلد. تهدف هذه الدراسة إلى تقييم معرفة طلاب الطب الجامعيين بالمخاطر المحتملة من التعرض للأشعة فوق البنفسجية وممارستهم لتدابير السلامة. أجريت دراسة في جامعة عمر المختار ، مدينة البيضاء ، ليبيا. شارك مائة وتسعة من طلاب الطب في هذه الدراسة فحص الاستبيان معرفة المشاركين وسلوكهم تجاه المخاطر المحتملة المرتبطة بالتعرض للأشعة فوق البنفسجية. النتائج.77.1 ٪ منهم من الإناث و 22.9 ٪ من الذكور. كانت غالبية المستجيبين أكثر من 22 سنة. فوق النصف 59.6 ٪ أظهروا معرفة معتدلة حول عواقب التعرض للأشعة فوق البنفسجية ، ومعظم الطلاب 91 ٪ يعرفون الآثار الجانبية للأشعة فوق البنفسجية على الصحة تليها 86 ٪ أشاروا إلى أن الأشعة فوق البنفسجية يمكن أن تسبب الشيخوخة المبكرة والسرطان. على النقيض من ذلك ، عرف أقل من الثلث أن الأشعة فوق البنفسجية لها تأثير سلبي على جهاز المناعة ، وحوالي الثلثين 73.9 ٪ لم يدركوا أن حروق الشمس يمكن أن تحدث حتى في م يوم غائم. على الرغم من أن طلاب الطب أظهروا مستوى معتدلا من المعرفة فيما يتعلق بالأشعة فوق البنفسجية، إلا أنه كان هناك نقص في استخدام تدابير السلامة النشطة من أشعة الشمس